Assessing the patient’s affective perception of their psychotherapist: validation of the in-Session Patient Affective Reactions Questionnaire - Stefana, Alberto; Fusar-Poli, Paolo; Vieta, Eduard; Youngstrom, Eric A. (Frontiers in Psychiatry, 2024)
Background: Psychotherapists need effective tools to monitor changes in the patient's affective perception of the therapist and the therapeutic relationship during sessions to tailor therapeutic interventions and improve treatment outcomes. This study aims to evaluate the factor structure, reliability, and validity of the in-Session Patient Affective Reactions Questionnaire (SPARQ), a concise self-report measure designed for practical application in real-world psychotherapy settings.Validation data was gathered from (N=700) adult patients in individual psychotherapy.These patients completed the SPARQ in conjunction with additional measures capturing sociodemographic details, characteristics of therapeutic interventions, individual personality traits, mental health symptom severity, elements of the therapeutic relationship, and session outcomes. This comprehensive approach was employed to assess the construct and criterion-related validity of the SPARQ.The SPARQ has a two-factor structure: Positive Affect (k=4, ω total=.87) and Negative Affect (k=4, ω total =.75). Bifactor confirmatory factor analysis (CFA) yielded the following fit indices: X 2 [df]=2.53, CFI=.99; TLI=.98; RMSEA=.05; and SRMR=.02. Multi-group CFAs demonstrated measurement invariance (i) across patients who attended psychotherapy sessions in person versus in remote mode, and (ii) across patients with and without psychiatric diagnoses confirmed metric invariance. Furthermore, the SPARQ showed meaningful correlations with concurrently administered measures.The SPARQ proves to be a valuable instrument in clinical, training, and research contexts, adept at capturing patients' session-level affective responses towards their therapist and perceptions of the therapeutic alliance. Comprehensive descriptive statistics and a range of score precision indices have been reported, intended to serve as benchmarks for future research.